Future of circular economy in Thailand: Evidence from corporate efforts - Salam, MD Abdus (Wisdom Journal of Humanities and Social Sciences, 2025)
This position paper advocates for the transition to a circular economy as a critical pathway for sustainable development, focusing on Thailand’s potential to emerge as a leader in Southeast Asia. The paper highlights the proactive role of leading Thai corporations, such as Siam Cement Group (SCG), in implementing circular economy principles to address environmental challenges and foster economic growth. Through an analysis of corporate strategies, this study underscores the adoption of sustainable manufacturing processes, resource optimization, and closed-loop systems. Key examples illustrate how innovative practices contribute to reducing waste and promoting product life cycle management. While Thailand has made significant progress, the paper identifies persistent challenges, including regulatory inconsistencies, limited consumer awareness, and infrastructural gaps. It argues that overcoming these barriers will require stronger collaboration between public and private stakeholders, alongside greater investments in research and development. This position paper advocates for Thailand to leverage its unique strengths to establish itself as a regional benchmark for sustainability. By aligning corporate efforts with supportive policies, Thailand can achieve not only environmental sustainability but also long-term economic resilience in a resource-constrained world.